2016
DOI: 10.1039/c6ra01276k
|View full text |Cite
|
Sign up to set email alerts
|

Iridium and rhodium “PNP” aminodiphosphine complexes used as catalysts in the oxidation of styrene

Abstract: New Ir and Rh “PNP” aminodiphosphine complexes are effective catalysts in styrene oxidation with tert-butyl hydroperoxide as the oxidant. The Ir catalysts were more active than the Rh catalysts with high yields to benzaldehyde in comparison to styrene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Our recent study on the application of these catalysts showed that these two families of complexes follow similar chemistry for styrene oxidation. 74 Therefore, 1a was only chosen for the initial optimization studies. The reaction was initially carried out at 80 °C with tert -butyl hydroperoxide (TBHP) as the oxidant in acetonitrile using catalyst 1a (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent study on the application of these catalysts showed that these two families of complexes follow similar chemistry for styrene oxidation. 74 Therefore, 1a was only chosen for the initial optimization studies. The reaction was initially carried out at 80 °C with tert -butyl hydroperoxide (TBHP) as the oxidant in acetonitrile using catalyst 1a (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…This clearly confirms the contribution of the nitrogen atoms of the ligands in these complexes in tuning the selectivity to certain products, besides the already discussed role in improving the catalyst basicity that was discussed in a previous study using these catalysts. 74 The deep oxidation process (ketone formation) is much slower with the rhodium catalysts in comparison to the Ir catalysts ( Figure 6), which is noted by the higher selectivity for the octanols (11%-41%), with catalyst 2b being the most selective (41%) and 2c being the least selective toward these octanols. As also noted with the iridium catalysts, the C(1) position is the least active, with the C(2) and C(3) positions being the most active carbons ( Table 1).…”
Section: Oxidation Of N-octanementioning
confidence: 96%
See 3 more Smart Citations